Contemporary Resource Management: Adaptive, Innovative, Participatory, and Interactive Strategies for Dealing With Unexpected Crises - Suwandi Suwandi (CV. Syntax Corporation Indonesia, 2023)
Unexpected challenges and crises can arise at any time and affect various aspects of life. Such crises require quick, appropriate and innovative responses from the parties involved. This research aims to identify and analyze the adaptive, innovative, participatory, and interactive strategies used in dealing with unexpected crises. This research uses qualitative research methods. The data collection technique was carried out by literature study obtained through Google Schoolar. The data obtained were then analyzed through three stages, namely data reduction, data presentation, and conclusion drawing. The results showed that there are several adaptive, innovative, participatory and interactive strategies that can be used to deal with unexpected crises, including forming an emergency response team consisting of various elements of the community, conducting effective communication and coordination with the community, using information technology to disseminate information and coordinate crisis management activities, developing an early warning system to anticipate the occurrence of a crisis and increasing the capacity of the community to deal with crises